Hydrothermal synthesis of hierarchical CoMoO4 microspheres and their lithium storage properties as anode for lithium ion batteries. (September 2019) - Wang, Jinkai; Xie, Sanmu; Liu, Ting; Yao, Tianhao; Zhu, Lei; Asiri, Abdullah M.; Marwani, Hadi M.; Han, Xiaogang; Wang, Hongkang
Highlights: Hierarchical CoMoO4 microspheres were prepared via a facile hydrothermal method. The as-prepared CoMoO4 electrode exhibited superior lithium storage properties when used as anodes for LIBs. The hierarchical structure of CoMoO4 can withstand the volume changes with good morphology preservation upon cycling. Abstract: Transition metal oxides have attracted extensive attention as promising anodes for lithium ion batteries (LIBs) owing to their low cost and high theoretical capacities. However, the large volume changes upon lithiation/delithiation cycling gradually causes the drastic particle pulverization in the electrodes, thus leading to the fast capacity fading and limiting their practical applications. Ternary metal oxides with enhanced electronic conductivity and multiple electrochemically active sites display stepwise lithium storage behaviors, thus efficiently alleviating the volume change induced electrode pulverization problem. Herein, we report the synthesis of hierarchical CoMoO4 microspheres assembled from nanosheets via a facile hydrothermal method and subsequently annealing. When used as anodes for LIBs, the CoMoO4 electrode exhibits superior lithium storage properties, delivering large reversible capacities of 1008 and 896 mA h/g at current densities of 200 and 500 mA/g after 50 cycles, respectively, and notably an exceptional rate capacity of 444 mA h/g at 2000 mA/g. Design of ternary metal oxides with different electrochemically active components and novel nanostructures might be an useful strategy for exploring high-performance LIB anode materials in the next-generation energy storage devices.